2020
DOI: 10.1016/j.energy.2020.117693
|View full text |Cite
|
Sign up to set email alerts
|

Wind power forecasting of an offshore wind turbine based on high-frequency SCADA data and deep learning neural network

Abstract: Accurate wind power forecasting is essential for efficient operation and maintenance (O&M) of wind power conversion systems. Offshore wind power predictions are even more challenging due to the multifaceted systems and the harsh environment in which they are operating. In some scenarios, data from Supervisory Control and Data Acquisition (SCADA) systems are used for modern wind turbine power forecasting. In this study, a deep learning neural network was constructed to predict wind power based on a very high-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 47 publications
(48 reference statements)
1
58
0
Order By: Relevance
“…ANNs, as one of the most commonly used methods for wind power prediction, can identify the non-linear relationships between input features and output data [22]. One of the reasons for the tendency to use neural networks is to avoid the complexity of the mechanical structure in wind turbines [23]. Typically, an ANN model consists of an input layer, one or more hidden layers [11], and an output layer, where the historical data/features are fed for training and testing (see Figure 1).…”
Section: Annsmentioning
confidence: 99%
See 4 more Smart Citations
“…ANNs, as one of the most commonly used methods for wind power prediction, can identify the non-linear relationships between input features and output data [22]. One of the reasons for the tendency to use neural networks is to avoid the complexity of the mechanical structure in wind turbines [23]. Typically, an ANN model consists of an input layer, one or more hidden layers [11], and an output layer, where the historical data/features are fed for training and testing (see Figure 1).…”
Section: Annsmentioning
confidence: 99%
“…Comparison results showed that IF is a more effective way of providing accurate forecasting, especially when the investigated data do not follow the normal distribution. In another paper [23], the authors critically evaluated eleven features from a 7 MW wind turbine in Scotland, including four wind speeds at different heights, average blade pitch angle, three measured pitch angles for three blades, ambient temperature, yaw error and nacelle orientation. The results revealed that the blade pitch angle had the greatest effect on the performance of the prediction model, even more than wind speed and wind shear.…”
Section: Hybrid Approachmentioning
confidence: 99%
See 3 more Smart Citations